TMS SMART: Scalp Mapping of Annoyance Ratings and Twitches caused by Transcranial Magnetic Stimulation - Meteyard, Lotte; Holmes, Nicholas P. (Elsevier, 2018)
Background: The magnetic pulse generated during transcranial magnetic stimulation (TMS) also stimulates cutaneous nerves and muscle fibres, with the most commonly reported side effect being muscle twitches and sometimes painful sensations. These sensations affect behaviour during experimental tasks, presenting a potential confound for ‘online’ TMS studies. New method: Our objective was to systematically map the degree of disturbance (ratings of annoyance, pain, and muscle twitches) caused by TMS at 43 locations across the scalp. Ten participants provided ratings whilst completing a choice reaction time task, and ten different participants provided ratings whilst completing a 'flanker' reaction time task. Results: TMS over frontal and inferior regions resulted in the highest ratings of annoyance, pain, and muscle twitches caused by TMS. We predicted the difference in reaction times (RT) under TMS by scalp location and subjective ratings. Frontal and inferior scalp locations showed the greatest cost to RTs under TMS (i.e., slowing), with midline sites showing no or minimal slowing. Increases in subjective ratings of disturbance predicted longer RTs under TMS. Critically, ratings were a better predictor of the cost of TMS than scalp location or scalp-to-cortex distance. The more difficult ‘flanker’ task showed a greater effect of subjective disturbance. Comparison with existing methods: We provide the data as an online resource (www.tms-smart.info) so that researchers can select control sites that account for the level of general interference in task performance caused by online single-pulse TMS. Conclusions: The peripheral sensations and discomfort caused by TMS pulses significantly and systematically influence RTs during single-pulse, online TMS experiments.